The prevalence of antimicrobial-resistant escherichia coli in pigs from Johore and Selangor - Bahaman, Abdul Rani; Liman, B. (Malaysian Society of Applied Biology, 1985)
Eighty-nine (91/102) percent of the Escherichia coli isolates obtained from pigs on 6 farms in Johore and Selangor were shown to be resistant to one or more of the antimicrobial agents tested. Of these, 84% were resistant to Tetracycline, 77% to Streptomycin, 72% to Sulphonamides, 26% to Neomycin, 13% to Chloramphenicol and none to Nalidixic Acid. Almost all of the E. coli isolates from the commercial farms were resistant to Tetracycline, Streptomysin and Sulphonamides. Multiple antimicrobial resistant E. coli was prevalent in the commercial pig farms whilst in the smallholders, single antibiotic resistant E. coli was more dominant. The high prevalence of antimicrobial resistant E. coli from the animals studied could be attributed to antibiotic supplements in the feeds and/or frequent antibiotic therapy. In both management systems, the piglets appeared to be the age group that harboured most of the antimicrobial resistant E. coli. Altogether 30 E. coli strains were identified from the 102 isolates.